Formative assessment in second language learning: a systematic review and an annotated bibliography - Vassiliou, Skevi (Language Center, Cyprus University of Technology, 2019)
The aims of this dissertation are: (a) to present an overview of as many works written about L2/FL Formative Assessment in recent times as all possible, from 2000 to 2017; (b) to provide researchers and practitioners interested in L2/FL Formative Assessment a solid background in the area, and more particularly how this topic has been treated by other researchers over the 17 years under review. (c) to contribute to the development of critical thinking about the topic, help in establishing the relevance and quality of the annotated material on the topic, and (d) to facilitate L2/FL FA researchers as well as practitioners to form an overview of the research in the area.
Keywords: Formative Assessment; Literature Review; Annotated Bibliography